Simmel: Bildung as the Form of Subjectivity - D’Andrea, Fabio (Simmel Studies, 2019)
This essay is composed of two parts: in the first I contend that Simmel was a representative of a cultural variant within Enlightenment modernity. Dumont has shown that there are several cultural variants born of the clash between former European traditional cultures and the modern set of universal values. This set and the variants are linked by a Wechselwirkung that modifies them all, thanks to the work of cross-representations. In the second part I argue that Simmel had German Bildung in mind when describing the shaping of subjectivity and the form of the life process and that Bildung is a cross-representation. As such it plays a major role in contemporary cultural processes which cannot be fully understood without appreciating its multidimensional complexity.